A 2-Study Psychometric Evaluation of the Modified Dementia Worry Scale. (26th February 2021) - Roberts, Jennifer R.; Maxfield, Molly
A modified version of the Dementia Worry Scale (DWS) used the terminology "Alzheimer's disease and related dementias" (versus the DWS' use of "dementia"). Two studies investigated psychometric properties of the modified DWS (MDWS). Study 1 compared the psychometric properties of the DWS and MDWS; both versions had single factor structures and exhibited excellent internal consistency (αs ≥ .95). The MDWS exhibited greater test-retest reliability after a 4-week interval (DWS r = .68; MDWS r = .90). In Study 2, the MDWS again displayed a single factor structure, excellent internal consistency (α = .95), and good test-retest reliability after an 8-week interval (r = .78). Additionally, results support convergent validity between the MDWS and fear of dementia, subjective memory, general anxiety, health anxiety, and neuroticism. The MDWS is psychometrically consistent with the DWS, maintains strong test-retest reliability, and is appropriate for use in cross-sectional and longitudinal research.